Undercarboxylated osteocalcin does not correlate with insulin resistance as assessed by euglycemic hyperinsulinemic clamp technique in patients with type 2 diabetes mellitus - Mori, Katsuhito (BioMed Central, 2012)
BACKGROUND: Recent in vitro and in vivo studies have suggested a critical role of osteocalcin (OC), especially the undercarboxylated form (ucOC), in insulin secretion and insulin sensitivity. The objective of this study was to investigate the association between serum ucOC levels and insulin resistance in humans with type 2 diabetes mellitus. FINDINGS: We measured serum ucOC levels in 129 patients with type 2 diabetes. Insulin resistance was assessed using the euglycemic hyperinsulinemic clamp technique. The insulin resistance indices used were the M value, which is the total body glucose disposal rate, and the M/I value, which is the M value adjusted for the steady state plasma insulin level. ucOC levels were not correlated with the M value (ρ = −0.013, p = 0.886) or the M/I value (ρ = 0.001, p = 0.995). CONCLUSIONS: We found no association between ucOC levels and insulin resistance in patients with type 2 diabetes mellitus.